Social impacts of mining: Changes within the local social landscape - Petrova, Svetla; Marinova, Dora (EContent Management Pty Ltd, 2013)
Understanding the social impacts at a community level triggered by mining operations is a challenging exercise. This paper reflects on a community’s perceptions and interpretation of these impacts as well as on the qualitative changes in the local social landscape and their implications for a sustainable future. The findings are based on an exploratory research carried out in a small established settlement in Western Australia. Considered as an agricultural community for decades, Boddington currently hosts two mining operations. Even though mining has been carried out there for decades, the recent opening of a large-scale mining operation is triggering significant demographic changes which result in a structural and functional transformation of the local social environment. Two new phenomena, namely transiency and a dependency culture are identified. Maintaining existing levels of social and economic capital as well as mobilising the community’s resources to capitalise on the opportunities associated with mining, are identified as key challenges for the settlement’s sustainability.